Unveiling the Catalytic Merits of LaV3O9 over Conventional LaVO4 Polymorphs to Boost Desired Kinetics of Humid NOX Reduction and Poison Disintegration - Lee, Seokhyun; Choi, Jeongeun; Ha, Heon Phil; Lee, Jung-Hyun; Park, Jongwook; Kim, Jongsik (American Chemical Society, 2024)
SOZ2？ (Z = 3？4)-functionalized metal vanadates vary with the type of metal cations (Mn+) for the Mn+-O2？-V5+ channels that fragment to impart Br？nsted acidic bonds (BA？-H+; SOZ2？-H+) and labile/mobile oxygens (OL/OM) with distinct populations and affinities for NOX/O2/H2O/SO2. SOZ2？-modified Mn+-O2？-V5+ fragments bind with NH3 to activate Eley？Rideal (ER)-type selective catalytic NOX reduction (SCR), yet, hardly enable OL coordination with NOX and are often hydrophilic, thereby limiting the activities of SCR or ammonium (bi)sulfate (AS/ABS) fragmentation, as gauged by the NOX consumption (-rNOX) and AS/ABS degradation rates (-rAS/ABS), respectively. Here, we justified the use of nonreducible La3+-containing La3+-O2？-V5+ channels, whose merits in accelerating SCR and AS/ABS fragmentation were found to be more pronounced for SOZ2？-modified LaV3O9 (LaV3O9-S) than for conventional/polymorphic LaVO4 analogues (LaVO4-S). Besides activating the ER-type SCR, LaV3O9-S bound with NO and activated Langmuir？Hinshelwood-type SCR, as opposed to LaVO4-S. The pre-exponential factor (k′APP,0) and -rNOX were thus higher for LaV3O9-S than for LaVO4-S and were coupled with the greater amount of OM in the former, leading to superior SCR performance under wet gases. Moreover, compared to LaV3O9-S, its Sb2O5-promoted analogue (LaV3O9-Sb2O5-S) provided a larger number of NH3-accessible BA？-H+ bonds to achieve higher k′APP,0/-rNOX alongside higher OM mobility. Furthermore, the LaV3O9-S and Sb2O5-S of LaV3O9-Sb2O5-S elevated the hydrophobicity and number of ABS-accessible BA？-H+ bonds, respectively. LaV3O9-Sb2O5-S thus revealed a lower energy barrier and higher k′APP,0 in AS/ABS pyrolysis than a commercial control (V2O5-WO3-S), resulting in a higher -rAS/ABS for the former. Consequently, LaV3O9-Sb2O5-S displayed superior SCR performance and greater hydrothermal resistance under SO2-containing wet gases in comparison with V2O5-WO3-S.